Structure-Based Function of Humic Acid in Abiotic Stress Alleviation in Plants: A Review - Farhan Nabi; Ahmed Sarfaraz; Rakhwe Kama; Razia Kanwal; Huashou Li (Plants)
Humic acid (HA), a major component of soil organic matter, is a naturally occurring macromolecule formed through the decomposition of plant and microbial residues. Its molecular structure comprises functional groups such as carboxyl, phenolic, hydroxyl, and carbonyl functional groups, which enable HA to interact with soil particles, nutrients, and biological systems. These interactions significantly contribute to soil fertility and overall plant productivity. Functionally, HA enhances soil health by increasing cation exchange capacity, improving water retention, and promoting the formation and stabilization of soil aggregates. In addition to its role in soil conditioning, HA is essential in mitigating plant stress. It achieves this by modulating antioxidant enzyme activity, stabilizing cellular membranes, and alleviating the adverse effects of abiotic stressors such as salinity, drought, and heavy metal toxicity. This review highlights the structural characteristics of HA, its structure-based functions, and the mechanisms involved in plant stress alleviation. Additionally, we explore how HA can be modified through physical, chemical, and biological approaches to enhance its agronomic performance. These modifications are designed to improve HA agronomic efficiency by increasing nutrient bioavailability, reducing environmental losses through minimized leaching and volatilization, and supporting sustainable agricultural practices. Overall, this review underscores the multifaceted roles of HA in promoting plant resilience to environmental stress, highlighting its potential as a key agent in the development of sustainable and eco-friendly crop production systems.